2015
DOI: 10.1016/j.exer.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of glucocorticoid-induced glaucoma

Abstract: Glucocorticoid (GC) therapy is widely used to treat a variety of inflammatory diseases and conditions. While unmatched in their anti-inflammatory and immunosuppressive activities, GC therapy is often associated with the significant ocular side effect of GC-induced ocular hypertension (OHT) and iatrogenic open-angle glaucoma. Investigators have generated GC-induced OHT and glaucoma in at least 8 different species besides man. These models mimic many features of this condition in man and provide morphologic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 92 publications
0
52
0
Order By: Relevance
“…Animal models can provide better insights into pathogenesis of GC-induced OHT, and investigators have reported GC-OHT in eight different species besides human. 4 In our study, we describe a mouse model of GC-OHT with a novel periocular CF delivery of DEX-Ac. This reproducible model is easy to run and captures many aspects of GC-induced OHT, including elevated IOP, reduction in the aqueous humor outflow facility, and reversibility of ocular hypertension after discontinuing GC treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal models can provide better insights into pathogenesis of GC-induced OHT, and investigators have reported GC-OHT in eight different species besides human. 4 In our study, we describe a mouse model of GC-OHT with a novel periocular CF delivery of DEX-Ac. This reproducible model is easy to run and captures many aspects of GC-induced OHT, including elevated IOP, reduction in the aqueous humor outflow facility, and reversibility of ocular hypertension after discontinuing GC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…4 The routes of GC administration in treatment of these disorders can be topical ocular, oral, systemic, intravitreal injections and implants, and periocular injections (including subconjunctival, subtenon, retrobulbar, and peribulbar).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact pathophysiology is not fully understood, glucocorticoids appear to act directly on trabecular meshwork (TM) cells to influence cellular, biochemical, and molecular changes that ultimately lead to reduced outflow facility [3, 4]. Glucocorticoids alter the organization of the actin cytoskeleton and induce the formation of so-called cross-linked actin networks (CLANs) in TM, leading to increased outflow resistance [5].…”
Section: Discussionmentioning
confidence: 99%
“…While the nonhuman primate experimental glaucoma model (Burgoyne, 2015b) benefits from optic nerve head (ONH) anatomy and physiology that is similar to the human ONH, the model is impractical for studies that require large sample sizes. By contrast, rodent models (Crowston et al, 2015; Fernandes et al, 2015; Morgan and Tribble, 2015; Morrison et al, 2015; Overby and Clark, 2015; Pang et al, 2015) display pathophysiologic changes that are comparable to human glaucoma, despite substantial differences in ONH anatomy.…”
Section: Introductionmentioning
confidence: 99%